The Contribution of Mass Organization to the Improvement of SMEs Business (A Case Study on KJKS Ankasa GP. Ansor of Pekalongan Regency) - Jumailah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
This article aims to find out the contribution of mass organization to the improvement ofSME business in KJKS Ankasa GP. Ansor of Pekalongan Regency. This study was aqualitative research with case study approach. The subject of research was Sharia-basedFinancial Service Cooperatives (Koperasi Jasa Keuangan Syariah, thereafter called KJKS)Ankasa, while the object was GP Ansor of Pekalongan Regency. The result of researchshowed that GP Ansor of Pekalongan Regency can empower the existing economic potencyof members, by means of developing pro-people economy, establishing KJKS. The presenceof KJKS can reduce unemployment rate, by providing funding help. The fund grant is givento the members having expertise (skill) but having no capital. To the public, this KJKSAnkasa is a means of providing capital, particularly to small-to-medium scale employers thatfacilitates them in the term of financing. To GP. Ansor, the presence of KJKS is beneficialto the distribution of fund for social activity (social service) purpose. KJKS Ankasa’s businessactivity includes financing, investment, and saving corresponding to profit sharing (sharia)pattern and aiming to achieve organizational independency.